Prevention of Stunting through Improving Maternal Parenting and Early Detection of Pregnancy Risk Factors - Inggil Wirya Pranata; Rizqy Aiddha Yuniawati; Nala Auna Robbika; Galih Haryo Permadi; Mochamad Nuril Anwar; Rachel Ariela Davy Eka Putri; Hikma Urwatil Wusqo; Sausan Syahira Arsyie; Nisrin Novel; Sylvi Maria Fransisca (Jurnal Pengabdian Masyarakat Bestari, 2022)
According to recommendations from the Jember Regency Government and the results of a field survey, stunting is one of the most pressing issues facing the community, particularly in the deployment area of Kemuningsari Kidul Village, Jenggawah, Jember. As part of an activity program, the villagers of Kemuningsari Kidul will receive counseling to prevent stunting by enhancing maternal parenting and detecting pregnancy risk factors early on. This activity aims to increase pregnant women's knowledge of stunting, preventative measures, and the definition of stunting in order to eliminate confusion among mothers. It is hoped that the program will be able to reduce the incidence of stunting in Jember and prevent its recurrence.